Gods of Egypt [videorecording (DVD)] - Coster-Waldau, Nikolaj, 1970-; Thwaites, Brenton, 1989-; Boseman, Chadwick; Butler, Gerard, 1969-; Rush, Geoffrey, 1951-; Brown, Bryan, 1947- (Summit Entertainment ; Lionsgate, 2016)
In this spectacular action-adventure inspired by the classic mythology of Egypt, the survival of mankind hangs in the balance as an unexpected mortal hero Bek undertakes a thrilling journey to save the world and rescue his true love. In order to succeed, he must enlist the help of the powerful god Horus in an unlikely alliance against Set, the merciless god of darkness, who has usurped Egypt's throne, plunging the once peaceful and prosperous empire into chaos and conflict.